Water Richness Zoning and Evaluation of the Coal Seam Roof Aquifer Based on AHP and Multisource Geological Information Fusion. (29th October 2021) - Zhou, Ke
Abstract : Roof water disaster is one of the most serious disasters in the process of coal mine safety mining in China. The thickness of modern comprehensive mechanized coal mining is large, which has a great impact on the roof aquifer, and the threat degree of water disaster is also increasing. Therefore, the evaluation of the water richness of the roof aquifer is an important work for coal mine water prevention and control. In order to systematically evaluate the water-rich property of an aquifer in a coal seam roof, this paper couples multisource geological information based on an analytic hierarchy process (AHP). The characteristics of the roof aquifer, hydrogeology, and structure are determined to be the main control factors of K2 limestone water richness evaluation. Under the main control factors, seven independent water richness evaluation indexes, including aquifer depth, aquifer thickness, borehole water level, borehole water consumption, faults, folds, and collapse columns, are divided, and a normalized water richness coupling evaluation model is constructed, which realizes the zoning and evaluation of a water-rich aquifer in a coal seam roof.